Prevalence and burden of chronic bronchitis symptoms: results from the BOLD study. Issue 5 (23rd November 2017) - Mejza, Filip; Gnatiuc, Louisa; Buist, A. Sonia; Vollmer, William M.; Lamprecht, Bernd; Obaseki, Daniel O.; Nastalek, Pawel; Nizankowska-Mogilnicka, Ewa; Burney, Peter G.J.
We studied the prevalence, burden and potential risk factors for chronic bronchitis symptoms in the Burden of Obstructive Lung Disease study. Representative population-based samples of adults aged ≥40 years were selected in participating sites. Participants completed questionnaires and spirometry. Chronic bronchitis symptoms were defined as chronic cough and phlegm on most days for ≥3 months each year for ≥2 years. Data from 24 855 subjects from 33 sites in 29 countries were analysed. There were significant differences in the prevalence of self-reported symptoms meeting our definition of chronic bronchitis across sites, from 10.8% in Lexington (KY, USA), to 0% in Ile-Ife (Nigeria) and Blantyre (Malawi). Older age, less education, current smoking, occupational exposure to fumes, self-reported diagnosis of asthma or lung cancer and family history of chronic lung disease were all associated with increased risk of chronic bronchitis. Chronic bronchitis symptoms were associated with worse lung function, more dyspnoea, increased risk of respiratory exacerbations and reduced quality of life, independent of the presence of other lung diseases. The prevalence of chronic bronchitis symptoms varied widely across the studied sites. Chronic bronchitis symptoms were associated with significant burden both in individuals with chronic airflow obstruction and those with normal lung function. Chronic bronchitis symptoms are associated with significant burden regardless of the presence of airflow obstruction http://ow.ly/kP9P30eFELK